Avaliação dos padrões de consumo de crack, cognição global e de funções executivas em usuários de ambulatório especializado de alta demanda - Moscon, Janine Andrade (2013)
Introduction: in 2012, there were disclosed the results from the first populational study regarding the intranasal and smoked cocaine use in Brazil. Apparently, the easy access, low cost and the pharmacokinetic profile similar to the intravenously injected cocaine (with lower risks of infectious disease transmission) led to the high commercial power of crack, even higher than the aspirated use of cocaine hydrochloride. Brazil, 25 years after the first apprehension of crack cocaine, has a prevalence of smoked cocaine (especially crack-cocaine) dependents about 380 thousand individuals. This refers to a population whose clinical-epidemiological features need to be more explored by researchers and physicians. Besides, the therapeutic approach has been complex and defiant. Method: this is a descriptive transversal study which included 72 crack users from a high-demand center performed between April 2011 and December 2012. The goal was to proceed an assessment of the psychoactive substance consume profile and a global cognitive and frontal executive function assessment of crack users. For this, it was performed a semi-structured interview in which clinic and socio-demographic data were collected. Besides, assessment tools as MMSE (global cognition), FAB (executive functions), and Hamilton Anxiety and Depression Scales were applied. Results & Conclusions: the present study observed an expansion of the age range of crack consume, especially the new finding of older subjects that are initiating the consume. The development of tolerance is evident since the amount of the rocks smoked per week shows gradual increase. The mean of global cognitive function did not change in relation to the expected populational average, however, there was a decrease in the frontal executive functions according to the time of use, especially in the inhibitory control. The depressive symptoms, in males, also increased together with the progress of the drug use and this was the factor that strongly correlated with the reduction in the period of abstinence